2015
DOI: 10.1242/jcs.177691
|View full text |Cite
|
Sign up to set email alerts
|

The formins FHOD1 and INF2 regulate inter- and intra-structural contractility of podosomes

Abstract: Podosomes are actin-rich adhesion structures that depend on Arp2/3-complex-based actin nucleation. We now report the identification of the formins FHOD1 and INF2 as novel components and additional actinbased regulators of podosomes in primary human macrophages. FHOD1 surrounds the podosome core and is also present at podosome-connecting cables, whereas INF2 localizes at the podosome cap structure. Using a variety of microscopy-based methods; including a semiautomated podosome reformation assay, measurement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 67 publications
1
41
0
1
Order By: Relevance
“…Our findings explain previous 3D super-resolution observations that indicated that the actin core of individual podosomes is dome-shaped (42). Moreover, we propose here that the pPM also includes the podosome cap, a substructure that has been identified previously based on the localiza- tion of the formin INF2 and the myosin-interacting proteins supervillin and LSP-1 at the apical site of the core (43)(44)(45). Like α-actinin, INF2 and supervillin are primarily associated with linear actin filaments supporting the notion that the pPM consists of this type of filaments.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings explain previous 3D super-resolution observations that indicated that the actin core of individual podosomes is dome-shaped (42). Moreover, we propose here that the pPM also includes the podosome cap, a substructure that has been identified previously based on the localiza- tion of the formin INF2 and the myosin-interacting proteins supervillin and LSP-1 at the apical site of the core (43)(44)(45). Like α-actinin, INF2 and supervillin are primarily associated with linear actin filaments supporting the notion that the pPM consists of this type of filaments.…”
Section: Discussionsupporting
confidence: 90%
“…In macrophages, INF2 associates with another adhesive structure, the podosome, which is involved in remodeling the extracellular matrix. Opposite to its effects on focal adhesions, depletion of INF2 from macrophages leads to larger and longer-lived podosomes, and decreased matrix degradation, while expression of INF2 bearing activating mutations promotes smaller, short-lived podosomes [Panzer et al, 2016]. INF2 has also been observed to localize to sarcomere Z-lines in neonatal primary mouse cardiomyocytes, although its importance for sarcomere organization was not reported [Rosado et al, 2014].…”
Section: Inf2 and Cellular Actin Structuresmentioning
confidence: 99%
“…Besides the FH2-mediated direct binding to the barbed end of the actin filament, Fhod1 is also able to bind directly to actin filaments via the N-terminal region (Takeya & Sumimoto, 2003), thereby promoting actin-filament bundling (Schönichen et al, 2013;Schulze et al, 2014). Through cooperation of the two actin-binding sites, Fhod1 contributes to regulation of cell adhesion and migration in various type of cells including cancer cells (Gardberg et al, 2013;Iskratsch et al, 2013;Koka et al, 2003;Panzer et al, 2016).…”
mentioning
confidence: 99%